Self-Care as Key to Others' Care: The Perspectives of Globally Situated Experienced Senior-Level Sport Psychology Practitioners. Issue 2 (3rd April 2019) - Quartiroli, Alessandro; Etzel, Edward F.; Knight, Sharon M.; Zakrajsek, Rebecca A.
Abstract : Engaging in self-care has been proposed as a means of counteracting work–life stress that can negatively impact efforts by sport psychology practitioners (SPPs) to effectively and ethically care for their clients. Utilizing Hill's Consensual Qualitative Research methodological approach, researchers examined the perceptions, experiences, and meanings that 20 internationally located, experienced, senior-level SPPs attributed to their self-care. The researchers identified 3 main domains: (a) defining self-care for SPPs, (b) describing the self-care challenges SPPs faced, and (c) identifying the strategies used to overcome those challenges. The experienced and senior-level practitioners participating in this study recognized a need to sustain a relatively balanced approach in their professional and personal lives. They presented a perspective of self-care as necessary to effectively support and provide care for clients. The SPPs identified self-care as an important contributor to their sport psychology professional quality of life. Study findings have implications for the well-being of both novice and more experienced SPPs.